Evaluation of the best-designed graded exercise test to assess peak treadmill speed - Peserico, Cecilia Segabinazi; Zagatto, Alessandro Moura [UNESP]; Machado, Fabiana Andrade (Thieme, 2015)
This study examined the influence of different speed increments during treadmill exercise tests on peak treadmill speed (Vpeak) and its relationship with a 1-h treadmill running performance. 18 male recreational and amateur runners (10-km running pace: 10–15 km·h−1) performed, in an alternate order, 3 continuous incremental exercise tests with different speed increments (0.5, 1.0 and 2.0 km·h−1) on a motorized treadmill to determine Vpeak. Thereafter they undertook a 1-h time trial on a treadmill. Vpeak was determined as either (a) the highest speed that could be maintained for a complete minute (Vpeak-60 s), (b) the speed of the last complete stage (Vpeak-C), or (c) the speed of the last complete stage added to the product of the speed increment and the completed fraction of the incomplete stage (Vpeak-P). The Vpeak values were highly influenced by the different speed-incremented rates and the Vpeak-P determined during the protocol comprising speed increments of 1 km·h−1 presented the highest correlation with 1-h time trial performance (r=0.89). The results suggest that a protocol with speed increments comprising 1 km·h−1 and with a 3-min stage duration should be used as standard for the determination of Vpeak to assess aerobic fitness and predict endurance performance in recreational runners. Furthermore, the Vpeak-P should be used for the determination of Vpeak.
Keywords: Physical endurance; Running; Exercise test; Athletic performance; Sports physiology